Safety and efficacy of FRA® Octazyme C Dry (α‐galactosidase, α‐amylase, endo‐1, 3(4)‐β‐glucanase, endo‐1, 4‐β‐glucanase, mannan‐endo‐1, 4‐β‐mannosidase, pectinase, protease, endo‐1, 4‐β‐xylanase) for chickens for fattening and weaned piglets. (2nd August 2017) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: FRA ® Octazyme C Dry is a product that presents α‐galactosidase, α‐amylase, endo‐1, 3(4)‐β‐glucanase, endo‐1, 4‐β‐glucanase, mannan‐endo‐1, 4‐β‐mannosidase, pectinase, protease and endo‐1, 4‐β‐xylanase. It is intended to be used as a zootechnical additive for chickens for fattening and weaned piglets. The enzymes present in the additive are obtained from six different fermentation processes with four different microorganisms, Trichoderma citroviride, Aspergillus niger, Bacillus licheniformis and Bacillus amyloliquefaciens . In the tolerance and efficacy trials done in the target species, major limitations on the analysed enzyme activities in the feed were identified. These limitations did not permit the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) to conclude on the safety and efficacy of FRA ® Octazyme C Dry for the target species. The Panel concluded that the additive raises no concerns for the consumers of food products obtained from animals fed with the additive. No specific data were submitted to address the safety for the user, in the absence of such data the FEEDAP Panel could not conclude on the potential of the additive to be irritant to the skin and eyes or on its skin sensitising properties. Owing to the nature of the active substances, the additive should be considered a potential respiratory sensitiser. The use of FRA ® Octazyme C Dry as a feed additive poses no risks to the environment.